Gender Comparison of Psychological Reaction Between Breast Cancer Survivors and Their Spouses - Simin, Tan; Jin, Yan; Aidi, Zhang; Xiaofang, Tan; Chunhong, Ruan; Lezhi, Li (Frontiers in Psychology, 2021)
Background: Scant evidence exists among the different psychological issues between patients with breast cancer and their spouses. The objective of our study was to develop the measuring Instrument testing psychological reaction and compare the difference in psychological reaction between patients with breast cancer and their spouses during the period of diagnosis and treatment. Method: The semi-structured interview guideline was guided by the psychological stress model. In-depth interviews were conducted among patients with breast cancer and their spouses. Qualitative data was used to establish the item pool for the psychological reaction. Delphi method was used for item modifications. The items were conducted to find common factors through exploration factor analysis. Comparing the differences of common factors through T-test between patients with breast cancer and their spouses. Results: 5 couples were interviewed directed by the semi-structured interview guideline. 38 items were reserved to formulate the questionnaire through the Delphi method. A total of 391 respondents (216 patients and 175 spouses) were recruited to complete the questionnaire. 2 common structures were found through exploration factor analysis which was named as reaction to role and body image change and negative coping reaction. T-test found that the dimension of reaction to role and body image change (95% CI=2.34 to 5.01, p＜0.001) reflects the difference between breast cancer patients and their spouses. Conclusion: The reactions to role and body image change between patients with breast cancer and their spouses are different during the period of diagnosis and treatment. Clinical workers should pay attention to the different reactions and help couples deal with breast cancer smoothly.